2019
DOI: 10.1038/s41592-019-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

One-step generation of modular CAR-T cells with AAV–Cpf1

Abstract: Enhancing production efficiency, stability, effector function, and other desired features is of prime interest for chimeric antigen receptor engineered T cells (CAR-Ts). Here, we developed a new system for efficient generation of CAR-T with significantly enhanced features by streamlined genome engineering. Leveraging tracrRNA-independent CRISPR/Cpf1 systems with adeno-associated virus (AAV), building a stable CAR-T with homology-directed repair (HDR) knockin and checkpoint knockout (KIKO CAR-T) was achieved at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 36 publications
2
120
1
3
Order By: Relevance
“…Cas12a can be programmed to induce DNA doublestrand breaks (DSBs) at specific genomic loci in vivo [14,15,17,18,20,25,26]. To test if CeCas12a and BfCas12a could be harnessed for gene editing in mammalian cells, we optimized the codons of two genes and attached a Cterminal and an N-terminal nuclear localization signals (NLS) for optimal expression and nuclear targeting in human cells.…”
Section: Gene Editing With Cecas12a and Bfcas12a In Human Cellsmentioning
confidence: 99%
“…Cas12a can be programmed to induce DNA doublestrand breaks (DSBs) at specific genomic loci in vivo [14,15,17,18,20,25,26]. To test if CeCas12a and BfCas12a could be harnessed for gene editing in mammalian cells, we optimized the codons of two genes and attached a Cterminal and an N-terminal nuclear localization signals (NLS) for optimal expression and nuclear targeting in human cells.…”
Section: Gene Editing With Cecas12a and Bfcas12a In Human Cellsmentioning
confidence: 99%
“…Applying CRISPR‐Cas9 under ex vivo conditions may be technically less challenging but equally valuable for disease therapy. For instance, ex vivo genome editing in hematopoietic stem cells (HSCs) could potentially provide a cure for patients carrying sickle cell disease (SCD) and β‐thalassaemia, and targeted insertions via CRISPR strategies may provide a valuable alternative to T‐cell engineering for cancer immunotherapy . A proof‐of‐concept study by Dewitt et al has reported an efficient correction of the E6V mutation at sickle alleles in patients' HSCs, through CRISPR‐HDR‐based replacement with the assistance of oligonucleotide donors.…”
Section: High‐efficiency Genome Editing and New Applications Enabled mentioning
confidence: 99%
“…A proof‐of‐concept study by Dewitt et al has reported an efficient correction of the E6V mutation at sickle alleles in patients' HSCs, through CRISPR‐HDR‐based replacement with the assistance of oligonucleotide donors. Using AAV‐delivered Cpf1, Dai et al built stable CAR‐T cells with immune‐checkpoint knockout (KIKO CAR‐T cells) via the HDR‐based strategy in one step.…”
Section: High‐efficiency Genome Editing and New Applications Enabled mentioning
confidence: 99%
See 1 more Smart Citation
“…The Sadelain group inserted a CAR into the TRAC locus by electroporating T cells with Cas9/gRNA RNPs and delivering the CAR transgene using rAAV6 (Eyquem et al 2017). The Chen group also recently generated CAR-T cells by electroporating Cpf1 mRNA while delivering gRNA and donor DNA sequences via AAV, a method which enabled genetic disruption of a second location (Dai et al 2019). The Marson lab similarly delivered Cas9/gRNA RNP into T cells and used high-output PCR products as donor templates to correct a pathological IL2RA defect and replace endogenous TCR genes with a cancer antigen-specific transgenic TCR (Roth et al 2018).…”
Section: Introductionmentioning
confidence: 99%